A Mixture of Pure, Isolated Polyphenols Worsens the Insulin Resistance and Induces Kidney and Liver Fibrosis Markers in Diet-Induced Obese Mice - Hèctor Sanz-Lamora; Pedro F. Marrero; Diego Haro; Joana Relat (MDPI AG, 2022)
Obesity is a worldwide epidemic with severe metabolic consequences. Polyphenols are secondary metabolites in plants and the most abundant dietary antioxidants, which possess a wide range of health effects. The most relevant food sources are fruit and vegetables, red wine, black and green tea, coffee, virgin olive oil, and chocolate, as well as nuts, seeds, herbs, and spices. The aim of this work was to evaluate the ability of a pure, isolated polyphenol supplementation to counteract the pernicious metabolic effects of a high-fat diet (HFD). Our results indicated that the administration of pure, isolated polyphenols under HFD conditions for 26 weeks worsened the glucose metabolism in diet-induced obese mice. The data showed that the main target organ for these undesirable effects were the kidneys, where we observed fibrotic, oxidative, and kidney-disease markers. This work led us to conclude that the administration of pure polyphenols as a food supplement would not be advisable. Instead, the ingestion of complete "whole" foods would be the best way to get the health effects of bioactive compounds such as polyphenols.